2018
DOI: 10.1038/s41467-018-04415-1
|View full text |Cite
|
Sign up to set email alerts
|

Cellular conditions of weakly chelated magnesium ions strongly promote RNA stability and catalysis

Abstract: Most RNA folding studies have been performed under non-physiological conditions of high concentrations (≥10 mM) of Mg2+free, while actual cellular concentrations of Mg2+free are only ~1 mM in a background of greater than 50 mM Mg2+total. To uncover cellular behavior of RNA, we devised cytoplasm mimic systems that include biological concentrations of amino acids, which weakly chelate Mg2+. Amino acid-chelated Mg2+ (aaCM) of ~15 mM dramatically increases RNA folding and prevents RNA degradation. Furthermore, aaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(121 citation statements)
references
References 50 publications
5
103
1
Order By: Relevance
“…Mechanisms of Mg 2+ ‐regulated crowding effects on transcription and translation are still unclear. Recent studies on the effect of Mg 2+ on tRNA folding might provide some clues . Strulson et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms of Mg 2+ ‐regulated crowding effects on transcription and translation are still unclear. Recent studies on the effect of Mg 2+ on tRNA folding might provide some clues . Strulson et al.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanisms of Mg 2+ -regulated crowding effects on transcription and translation are still unclear. Recent studies on the effect of Mg 2+ on tRNA folding might provide some clues [28][29][30]. Strulson et al reported that 20% of PEG or dextran increased tRNA folding cooperativity under physiologically low concentrations of Mg 2+ (0.5-2 mM) and K + (140 mM) [28].…”
Section: Figmentioning
confidence: 99%
“…Given its rapid dissociation rate constant, the divalent ion therefore will quickly equilibrate between many Mg 2+ ‐binding sites in the cell (Figure ) so that a chelating detection probe is subject to competition for binding of Mg 2+ , especially from those competitors with a higher affinity for Mg 2+ or a higher concentration than the probe itself (Figure ). An example is the recent observation that amino acid chelated Mg 2+ pools are readily functional in promoting RNA folding and function . What fraction of Mg 2+ is detected as “free” will therefore be extremely sensitive to both the probe used and all diverse molecular species present in the cell at the time, as well as the molecular characteristics of their individual Mg 2+ binding sites.…”
Section: Biological Specificity Refined By Diverse Cellular Interactmentioning
confidence: 99%
“…An example is the recent observation that amino acid chelated Mg 2+ pools are readily functional in promoting RNA folding and function. [75] What fraction of Mg 2+ is detected as "free" will therefore be extremely sensitive to both the probe used and all diverse molecular species present in the cell at the time, as well as the molecular characteristics of their individual Mg 2+ binding sites. It is no wonder that much ambiguity arises from such measurements.…”
Section: Biological Specificity Refined By Diverse Cellular Interactmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The catalytic reaction of ribozymes proceeds in the presence of divalent metal ions, such as Mg 2+ , and even in the presence of Mg 2+ complexes coordinated by amino acids or diphosphate molecules. 9,10 Since ribozymes can selectively cleave RNA substrates, synthetic small constructs of transacting ribozymes are useful for developing oligonucleotidebased technologies, for example, for the in vivo inhibition of gene functions and for the construction of biosensor probes. [11][12][13] To maximize applications of ribozymes for biotechnology, it is important to develop methods to enhance their catalytic performance.…”
Section: Introductionmentioning
confidence: 99%